HEALTH EDUCATION INCREASES KNOWLEDGE OF HYPERTENSION AMONG THE HEALTH CADRES - Warsini, Warsini; Kristanto, Budi; Diyono, Diyono; Kristiani, Rina Budi; Iswati, Iswati (SYNTIFIC, 2025)
Background. From year to year, the number of cases of kronis in Indonesia is increasing, and the number of cases of hypertension is at an all-time high. The role of the health cadre is extremely important for the community, supporting health initiatives in both prevention and promotion. This community service aimed to increase knowledge of hypertension among health cadres. Implementation Method. The community service activity was carried out for 2 months, from September 1 to November 10, 2025. There were 29 health cadres participating in the activity, in partnership with the Plombokan Village in Semarang. Health cadres was given health education about hypertension and role of supportive-educative for patients hypertension; 6) guidance and assistance for cadres in implementing health programs aimed at improving the quality of life of patients with chronic diseases in the community. Findings. The level of health cadres' knowledge about hypertension, namely the average knowledge score of cadres, also increased from 70.34 before the activity to 75.86 after the activity. The results of the paired t-test showed a significant p-value = 0.002 (? ? 0.05), suggesting that hypertension health education increased the knowledge of health cadres. Conclusion. Through a combination of several activities in this community service program, cadres showed significant improvement in their knowledge and skills in managing chronic diseases and the Plombokan Village community, thereby improving the quality of life of patients with chronic diseases.